Why Is There No Cure for Tinnitus? - McFerran, Don J.; Stockdale, David; Holme, Ralph; Large, Charles H.; Baguley, David M (Frontiers in Neuroscience, 2019)
Tinnitus is unusual for such a common symptom in that there are few treatment options and those that are available are aimed at reducing the impact rather than rather than specifically addressing the tinnitus percept. In particular, there is no drug recommended specifically for the management of tinnitus. Whilst some of the currently available interventions are effective at improving quality of life and reducing tinnitus-associated psychological distress most show little if any effect on the primary symptom of subjective tinnitus loudness. Studies of the delivery of tinnitus services have demonstrated considerable end-user dissatisfaction and a marked disconnect between the aims of healthcare providers and those of tinnitus patients: patients want their tinnitus loudness reduced and would prefer a pharmacological solution over other modalities. Several studies have shown that tinnitus confers a significant financial burden on healthcare systems and an even greater economic impact on society as a whole. Market research has demonstrated a strong commercial opportunity for an effective pharmacological treatment for tinnitus, but the amount of tinnitus research and financial investment is small compared to other chronic health conditions. There is no single reason for this situation, but rather a series of impediments: tinnitus prevalence is unclear with published figures varying from 5.1% to 42.7%; there is a lack of a clear tinnitus definition and there are multiple subtypes of tinnitus, potentially requiring different treatments; there is a dearth of biomarkers and objective measures for tinnitus; treatment research is associated with a very large placebo effect; the pathophysiology of tinnitus is unclear; animal models are available but research in animals frequently fails to correlate with human studies; there is no clear definition of what constitutes meaningful change or “cure”; the pharmaceutical industry cannot see a clear pathway to distribute their products as many tinnitus clinicians are non-prescribing audiologists. To try and clarify this situation, highlight important areas for research and prevent wasteful duplication of effort, the British Tinnitus Association (BTA) has developed a Map of Tinnitus. This is a repository of evidence-based tinnitus knowledge, designed to be free to access, Intuitive and easy to use, adaptable and expandable.